The influence of intercalating perfluorohexane into lipid shells on nano and microbubble stability. Issue 34 (8th August 2016) - Abou-Saleh, Radwa H.; Peyman, Sally A.; Johnson, Benjamin R. G.; Marston, Gemma; Ingram, Nicola; Bushby, Richard; Coletta, P. Louise; Markham, Alexander F.; Evans, Stephen D.
Abstract : Incorporating C6 F14 into the lipid shell of microbubbles enhances the in vivo lifetime by reducing surface tension. It saturates the medium and reduces diffusivity of C4 F10 . Abstract : Microbubbles are potential diagnostic and therapeutic agents. In vivo stability is important as the bubbles are required to survive multiple passages through the heart and lungs to allow targeting and delivery. Here we have systematically varied key parameters affecting microbubble lifetime to significantly increase in vivo stability. Whilst shell and core composition are found to have an important role in improving microbubble stability, we show that inclusion of small quantities of C6 F14 in the microbubble bolus significantly improves microbubble lifetime. Our results indicate that C6 F14 inserts into the lipid shell, decreasing surface tension to 19 mN m −1, and increasing shell resistance, in addition to saturating the surrounding medium. Surface area isotherms suggest that C6 F14 incorporates into the acyl chain region of the lipid at a high molar ratio, indicating ∼2 perfluorocarbon molecules per 5 lipid molecules. The resulting microbubble boluses exhibit a higher in vivo image intensity compared to commercial compositions, as well as longer lifetimes.